Leadership in a Changing World [Working Title] 2022
DOI: 10.5772/intechopen.101989
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Values and Understandings from an Islamic Perspective

Abstract: This writing proposes the life of the Prophet Muhammad (peace be upon him) as a leadership framework for developing the concept of Rabbani’s leadership. The development of the leadership framework begins with the spiritual aspect, which is very closely related to the faith. Rabbani’s character in the leadership shown by Prophet Muhammad (PBUH) so emphasizes the spiritual aspect with a different approach from ordinary spiritual values. The faith generates Rabbani’s characteristics that influence the leadership … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Religious education can provide fundamental moral values needed in the business world such as honesty, integrity, responsibility, hard work, justice, and sacrifice (Salamun & Ab Rahman, 2022) and (Taufik, 2020). These values can shape MSME owners into figures who have high integrity, adhere to moral and ethical values in doing business, and have a strong commitment to running a good business.…”
Section: Resultsmentioning
confidence: 99%
“…Religious education can provide fundamental moral values needed in the business world such as honesty, integrity, responsibility, hard work, justice, and sacrifice (Salamun & Ab Rahman, 2022) and (Taufik, 2020). These values can shape MSME owners into figures who have high integrity, adhere to moral and ethical values in doing business, and have a strong commitment to running a good business.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Allah is all-knowing, all aware. 43 And had your Lord wished, all those who are on earth would have believed. Would you then force people until they become faithful?.…”
Section: The Farewell Pilgrimage Sermon's Role In Universal Human Rig...mentioning
confidence: 99%
“…This approach cultivates an environment conducive to personal and professional development within the organizational realm. 66 Islamic leadership principles aren't confined to theory but extend into organizational practices, demanding leaders to uphold values like security, openness, efficiency, and fair justice. Nonetheless, observations point to reduced interaction between leaders and employees, resulting in performance issues.…”
Section: Islamic Leadership: Mediation and Peace-building In Religiou...mentioning
confidence: 99%
“…Previous research has learnt that leadership in Islam is "a process to inspire and train followers voluntarily to achieve a clear and defined shared vision" (Beekun & Badawi, 1999). Moreover, different studies have shown that the Life of Prophet Muhammad (PBUH) is often proposed as a leadership framework to develop the concept of Rabbani leadership (Salamun & Rahman, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%